Role of Beneficial Microorganisms and Salicylic Acid in Improving Rainfed Agriculture and Future Food Safety - Naeem Khan; Asghari Bano; José Alfredo Curá (Microorganisms, 2020)
Moisture stress in rainfed areas has significant adverse impacts on plant growth and yield. Plant growth promoting rhizobacteria (PGPR) plays an important role in the revegetation and rehabilitation of rainfed areas by modulating plant growth and metabolism and improving the fertility status of the rhizosphere soils. The current study explored the positive role of PGPR and salicylic acid (SA) on the health of the rhizosphere soil and plants grown under rainfed conditions. Maize seeds of two different varieties, i.e., SWL-2002 (drought tolerant) and CZP-2001 (drought sensitive), were soaked for 4 h prior to sowing in 24-h old culture of Planomicrobium chinense strain P1 (accession no. MF616408) and Bacillus cereus strain P2 (accession no. MF616406). The foliar spray of SA (150 mg/L) was applied on 28-days old seedlings. The combined treatment of the consortium of PGPR and SA not only alleviated the adverse effects of low moisture stress of soil in rainfed area but also resulted in significant accumulation of leaf chlorophyll content (40% and 24%), chlorophyll fluorescence (52% and 34%) and carotenoids (57% and 36%) in the shoot of both the varieties. The PGPR inoculation significantly reduced lipid peroxidation (33% and 23%) and decreased the proline content and antioxidant enzymes activities (32% and 38%) as compared to plants grown in rainfed soil. Significant increases (>52%) were noted in the contents of Ca, Mg, K Cu, Co, Fe and Zn in the shoots of plants and rhizosphere of maize inoculated with the PGPR consortium. The soil organic matter, total nitrogen and C/N ratio were increased (42%), concomitant with the decrease in the bulk density of the rhizosphere. The PGPR consortium, SA and their combined treatment significantly enhanced the IAA (73%) and GA (70%) contents but decreased (55%) the ABA content of shoot. The rhizosphere of plants treated with PGPR, SA and consortium showed a maximum accumulation (>50%) of IAA, GA and ABA contents, the sensitive variety had much higher ABA content than the tolerant variety. It is inferred from the results that rhizosphere soil of treated plants enriched with nutrients content, organic matter and greater concentration of growth promoting phytohormones, as well as stress hormone ABA, which has better potential for seed germination and establishment of seedlings for succeeding crops.